How to factor the following expression: x^12 + x^6 - 2 ?

I really don't know how to start.

Luke.

How to factor the following expression: x^12 + x^6 - 2 ?

I really don't know how to start.

Luke.

I really don't know how to start.

Luke.

- maggiemagnet
**Posts:**306**Joined:**Mon Dec 08, 2008 12:32 am-
**Contact:**

Luke53 wrote:How to factor the following expression: x^12 + x^6 - 2 ?

I really don't know how to start.

How would you factor y^2 + y - 2? Now let x^6 = y.

How would you factor y^2 + y - 2? Now let x^6 = y.

I'll give it a try:

The factors of 2 are: 1 ; 2 and -1 ; -2 if I combine -1 and 2, the factors of the given quadratic are: (y - 1)(y + 2) expanding this gives: y² + y - 2 ; subst. y = x^6 gives: (x^6 - 1) (x^6 + 2).

To factor anything further out: ( x^6 + 2) won't factor into anything of the first degree, (just leaving it in this form).

Now : (x^6 - 1) ; I'll first check if 1 and -1 are roots of this expression: (x = 1) ; (1^6) - 1 = 0 so 1 is a root; ( x = -1) ; (-1^6) - 1 = 0, so -1 is also a root. Multiply these (x + 1) (x - 1) = (x^2 - 1).

I'll divide (x^6 -1 ) by (x^2 - 1) the result is: x^4+ x^2 + 1 this factors in to (x² + x + 1) (x² - x + 1).

So: x^12 + x^6 - 2 = (x + 1) (x - 1) (x² + x + 1) (x² - x + 1) (x^6 +2).

Thanks.

Luke.